A Comprehensive School-Based Nutrition Intervention to Improve the Implementation of Healthy School Canteen Policy: A Systematic Review - Tauhidah, Sarah At; Candi, Cicilya; Bachtiar, Adang (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: School-based nutrition intervention is recommended as one of the public health strategies in supporting the development of healthy diet behaviour for school-age children. It is in line with Global Action Plan 2013-2020 of World Health Organization (WHO) in preventing and controlling double burden of disease as a consequence of non-communicable disease in the future. This study aims to identify the kind of comprehensive school-based nutrition intervention and analyze effectiveness of every study in improving policy implementation of healthy school canteen.Subjects and Method: This systematic review study was conducted from two electronic databases, namely Scopus and ProQuest with keywords of